2014
DOI: 10.2355/isijinternational.54.1621
|View full text |Cite
|
Sign up to set email alerts
|

On Melting of Electrodes during Electro-Slag Remelting

Abstract: In this paper a numerical investigations on the thermal state and on the tip shape of a melting electrode during electro-slag remelting are presented. In the first part the heat necessary to melt an electrode with a flat tip shape is calculated. It is shown that to keep a constant melting rate, the heat supplied to the electrode must be continuously changed. The results for different electrode descend rates, corresponding to different melting rates, are presented. In the second part the melting process was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 15 publications
1
35
0
1
Order By: Relevance
“…15,16) Kharicha et al solved the electromagnetic field with electric potential method coupled with a VOF model to track the motion of metal droplets and phase boundaries, and concluded that the highest magnetic field intensity appears at the surface of droplets. 17) Wang et al developed a laboratory scale 3D multiphase-magneto-hydrodynamic model considering the effect of metal droplets on electromagnetic field, [18][19][20][21] and studied the multiphase flow and solidification in ESR process. Glesselmann et al studied the movement of droplets and solidification process using coupled multi zone models, which were solved with different time steps.…”
Section: Effects Of Metal Droplets On Electromagnetic Field Fluid Flmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16) Kharicha et al solved the electromagnetic field with electric potential method coupled with a VOF model to track the motion of metal droplets and phase boundaries, and concluded that the highest magnetic field intensity appears at the surface of droplets. 17) Wang et al developed a laboratory scale 3D multiphase-magneto-hydrodynamic model considering the effect of metal droplets on electromagnetic field, [18][19][20][21] and studied the multiphase flow and solidification in ESR process. Glesselmann et al studied the movement of droplets and solidification process using coupled multi zone models, which were solved with different time steps.…”
Section: Effects Of Metal Droplets On Electromagnetic Field Fluid Flmentioning
confidence: 99%
“…Additionally, the exposed slag surface and mould wall are assumed to be insulated excepted the electrode tip where the flux of electric potential is described. 17) The bottom boundaries and top boundaries share the identical magnetic field boundary condition, a magnetic induction flux of zero. The axial component of magnetic vector potential flux is prescribed at the mould wall, 16) where the radial component takes the value of zero.…”
Section: Electromagnetic Fieldmentioning
confidence: 99%
“…Most of the simulations [15][16][17][18][19][20][21][22][23][24][25] are focused on the analysis of the electromagnetic field, temperature distribution, flow pattern and profile of the metal pool. Their researches make people know the ESR process better, and then the ESR process may be improved by controlling the temperature distribution or the flow pattern to gain a better metal pool shape which will seriously affect the quantity of ingots.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kharicha et al [20] directly simulated the melting of electrode using the multiphase volume of fluid (VOF) method considering complex interactions between flow, temperature, and magnetic fields. It is found that the coupling between the Joule heat release and melting rate is very unstable.…”
Section: Introductionmentioning
confidence: 99%